(untitled) (Journal of Asian Development Studies, 2026)
The study aims to assess the present performance of the HR Team. The performance of the individual employees has been assessed through trend lines, with the help of various bar graphs. These charts were meant to provide the trend of individual employees, and configure areas of attention and improvement. The data used to examine the performance of the employees includes both primary and secondary data. For Primary data, a questionnaire was administered personally to all the Human Resource staff. For Secondary data various articles, books and websites were consulted the names of which are duly mentioned in the literature review and reference section. The sample size is 10. This includes 5 Executives, 2 Senior Executives and 3 Assistant Managers. For designing the Questionnaire Likert Scale was used. The questions are based on certain parameters such as innovation, vision, trust etc, which are essential elements of a High Performance team. To conclude, there should be more team bonding. There should be more transparency. More non- monetary rewards and recognitions should be introduced for motivational purposes. More training and developmental programs should be encouraged. There should be reduction in transactional work. Job rotation should be practiced more frequently. All this will lead to a high performance team. The management should work towards creating an environment where creativity is encouraged, increased people participation in the decision making process, development of trust among employees and provide more cross functional exposure.